DINAMIKA PERUMUSAN KEBIJAKAN PENDIDIKAN DI INDONESIA - Riska Meisyi Putri; Hidayatul Fadliah; Andri Ani Suryawijaya; Renny Yuliarti; Elfa Eriyani; Muhammad Ali Basroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this paper is to comprehensively describe the policy formulation process within the Indonesian education system. The national education system emphasizes that all forms of educational activities must be optimally organized and developed to achieve national education goals. In its implementation, sound decisions are required to ensure that the resulting policies are truly effective and aligned with the needs of the educational community. One crucial stage in the policy process is agenda setting, which serves to draw the government's attention to the various issues, challenges, and competition emerging in the world of education. This process requires a clear theoretical framework to ensure policy formulation has direction, a scientific basis, and measurable objectives. Thus, policy formulation in educational institutions can have strong legitimacy and be accountable. Furthermore, the success of education policy formulation is also greatly influenced by the roles of the actors involved and the approaches used at each stage of the policy process. Keywords: education policy, policy formulation, agenda setting